Brief Description of the Date of Origin Some Suffixes in Uzbek Language - Raupov Mexroj Xukumo‘g‘li (International Journal of Community Service & Engagement, 2021)
The article discusses the use of affixes in the modern Uzbek literary language, the views of linguists on affixes, the phonetic variants of affixes in Turkic languages, the origin of suffixes, based on existing scientific literature, case, detected.